Keeping Pace with Change : Fintech and the Evolution of Commercial Law - Garrido, Jose (International Monetary Fund, 2022)
This note explores the interactions between new technologies with key areas of commercial law and potential legal changes to respond to new developments in technology and businesses. Inspired by the Bali Fintech Agenda, this note argues that country authorities need to closely examine the adequacy of their legal frameworks to accommodate the use of new technologies and implement necessary legal reform so as to reap the benefits of fintech while mitigating risks. Given the cross-border nature of new technologies, international cooperation among all relevant stakeholders is critical. The note is structured as follows: Section II describes the relations between technology, business, and law, Section III discusses the nature and functions of commercial law; Section IV provides a brief overview of developments in fintech; Section V examines the interaction between technology and commercial law; and Section VI concludes with a preliminary agenda for legal reform to accommodate the use of new technologies.